2017
DOI: 10.1097/jsm.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Outlet Syndrome in the Overhead Athlete

Abstract: Subclavius posticus muscle is a supernumerary anatomical variation of the subclavius muscle. The aim of this study was to show the possible contribution of the posticus muscle in the development of unilateral thoracic outlet syndrome (TOS) in overhead athletes, presenting hypertrophy of the dominant arm due to their sport activity. Reported here are 2 young overhead athletes complaining pain, paresthesia, weakness in the dominant upper limb, although presenting none of the main shoulder and neurological disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Indeed, athletes combine nonspecific factors (such as cervical rib or coagulation anomaly) and more specific factors such as muscle hypertrophy, especially of the pectoralis minor, inducing the compression of the adjacent neurovascular bundle. This hypothesis is sustained by the frequent observation of muscle hypertrophy during TOS surgical procedure ( Katirji and Hardy, 1995 ; Ozcakar et al, 2005 ; Simovitch et al, 2006 ; Almeida et al, 2007 ; Aydoğ et al, 2007 ; Baltopoulos et al, 2008 ; Fitzgerald, 2012 ; Herbst and Miller, 2013 ; Jourdain et al, 2016 ; Norinsky et al, 2016 ; Ciampi et al, 2017 ). Bottros et al (2017) also proposed a diagnostic test of N-TOS based on ultra-sound guided scalenus anticus anesthesia.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, athletes combine nonspecific factors (such as cervical rib or coagulation anomaly) and more specific factors such as muscle hypertrophy, especially of the pectoralis minor, inducing the compression of the adjacent neurovascular bundle. This hypothesis is sustained by the frequent observation of muscle hypertrophy during TOS surgical procedure ( Katirji and Hardy, 1995 ; Ozcakar et al, 2005 ; Simovitch et al, 2006 ; Almeida et al, 2007 ; Aydoğ et al, 2007 ; Baltopoulos et al, 2008 ; Fitzgerald, 2012 ; Herbst and Miller, 2013 ; Jourdain et al, 2016 ; Norinsky et al, 2016 ; Ciampi et al, 2017 ). Bottros et al (2017) also proposed a diagnostic test of N-TOS based on ultra-sound guided scalenus anticus anesthesia.…”
Section: Resultsmentioning
confidence: 98%
“…One study reported that adding subclavius muscle resection to NTOS palliative treatment could improve results 13) . Another study suggested that botulinum toxin injections into the subclavius muscle could serve as a potential TOS treatment option 4) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, only 2 of the 25 items of the "Fantastic lifestyle assessment" tool relate to activity, one of which is not specific while the other concerns the lower limbs [51]. The only thing that is frequently reported in TOS series and case reports is the profession of the patient when the study deals with work-induced upper-limb disease and the types of sport activities pursued by athletes [52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Methods For Lifestyle Evaluation In the Clinical Routine Of ...mentioning
confidence: 99%